SOSIALISASI PENDIDIKAN NILAI DAN KARAKTER DI MASYARAKAT - Waluyo, Agus (El-Hamra, 2018)
The formulation of the problem of this paper is "How is the orientation and problems of education values and characters in the community, with the formulation of this problem it is hoped that it will find an answer to the problems of character and values that arise in the community. From the presentation of education socialization of values and characters, it can be found that some of the things expressed in this paper contain several things that we need to understand including: 1) That education of values and character is a process to direct someone towards goodness, good to others, others , environment and God Almighty. 2). That the orientation of values and character education aims to socialize positive values in the community so that they are able to form distinctive characters or characters with noble character. 3) Dissemination of values and character education in the community is carried out with relationship-based, cultural, and community-based character design.Key Words: Value and Character Education, Society